Application Model for Travel Recommendations Based on Android - Rahma Wahdiniwaty; Eko Budi Setiawan; Fajri Auliardi; Deden A Wahab (IJNMT (International Journal of New Media Technology), 2019)
Abstract—Traveling is a fun activity. Everyone has a different preference for the type of tour they like. Some like nature tourism, culinary tours, religious tourism, and other tourism. Problems encountered by tourists when planning tourism activities, usually do not know complete information related to tourist destinations that will be visited, and can not make weather forecasts from the destination tourist destination. This research aims to provide a model travel recommendation that is implemented into the Android mobile application so that tourists can be given recommendations on which tourism destinations are most suitable based on the criteria that are the assessment criteria, namely the price of tourist accommodation, weather and rating of tourist attractions. Mobile technology used is using GPS sensors, Google Maps API, Open WeatherMap API, and Facebook API. Based on the results of testing, the application in this research can help in recommending tourist attractions that meet the criteria desired by tourists.